ORIGINS OF THE LEGAL REGULATION OF RESIDENTIAL RELATIONS IN THE ANCIENT ROME (Bulletin of Kharkiv National University of Internal Affairs, 2018)
In order to establish the origin of residential legal relations within Roman law to clarify the nature of residential legal relations, in particular their independence, the author has analyzed the Roman law aiming at distinguishing residential relations from others that existed in regard buildings.It has been established that the categories and requirements of sanitary and technical character for buildings were determined in Ancient Rome; the concepts of “living in dwelling” and “use of housing” were distinguished; there were obligations on the use of housing and real rights to reside and use of housing; requirements for joint residence of family members were established; the rules for building and repair of housing were formulated; there was the possibility of interference with the public element in housing maintenance, etc.The contract of employment under the Roman law, the servitude of residence, the right to reside have been analyzed. Features of housing maintenance, passed for use, has been established. The basic rules that became the basis for the modern administrative norms in the field of accounting, control over the state of housing, providing assistance by the state in case of destruction of housing, the formation of state agencies in the field of construction control, housing, etc. have been found out.The existence of independent residential legal relations, which have a mixed private and public character, has been proved. The legal nature of housing in the dwelling depended on the grounds of residence (obligation or real right), it covered a number of powers: the use of housing in order to meet the housing needs; housing maintenance; transfer of housing for residence to other persons; obtaining profit.